Hepatic microcirculatory disturbance in liver diseases: intervention with traditional Chinese medicine - Liu, Pei; Liang, Wan-Li; Huang, Rui-Ting; Chen, Xin-Xing; Zou, De-Hua; Kurihara, Hiroshi; Li, Yi-Fang; Xu, You-Hua; Ouyang, Shu-Hua; He, Rong-Rong (Frontiers in Pharmacology, 2024)
The liver, a complex parenchymal organ, possesses a distinctive microcirculatory system crucial for its physiological functions. An intricate interplay exists between hepatic microcirculatory disturbance and the manifestation of pathological features in diverse liver diseases. This review updates the main characteristics of hepatic microcirculatory disturbance, including hepatic sinusoidal capillarization, narrowing of sinusoidal space, portal hypertension, and pathological angiogenesis, as well as their formation mechanisms. It also summarized the detection methods for hepatic microcirculation. Simultaneously, we have also reviewed the characteristics of microcirculatory disturbance in diverse liver diseases such as acute liver failure, hepatic ischemia-reperfusion injury, viral hepatitis, non-alcoholic fatty liver disease, hepatic fibrosis, hepatic cirrhosis, and hepatocellular carcinoma. Finally, this review also summarizes the advancement in hepatic microcirculation attributed to traditional Chinese medicine (TCM) and its active metabolites, providing novel insights into the application of TCM in treating liver diseases.